Comparative studies on physicochemical properties of gluten‐ and glutenin‐based films functionalized by polyphenols. Issue 3 (18th January 2022) - Liu, Xinye; Xie, Yuran; Li, Chen; Xue, Feng
Abstract: Background and objectives: This study aimed to develop gluten‐ and glutenin‐based active films functionalized individually by three different types of polyphenols (naringin, cyanidin‐3‐O‐glucoside, and proanthocyanidin). The interaction of these phenolic compounds with gluten and glutenin, and the effect of presence of these polyphenols on the physicochemical, antioxidative, and antimicrobial properties of resulting films were evaluated. Findings. The proanthocyanidin interacted with gluten and glutenin helped to form rougher surface structure and more homogeneous cross‐sectional structure. Therefore, the water vapor barrier property, water repellence, tensile strength, and thermal stability of the films were substantially improved in the presence of proanthocyanidin. The films containing proanthocyanidin also showed ability to inhibit growth of foodborne pathogens and scavenge free radical. Furthermore, the glutenin films exhibited higher tensile strength and better thermal stability. The gluten films possessed better water vapor barrier property and water repellence. Conclusion: There were significant differences in physical properties between gluten films and glutenin films due to the difference of composition. However, the effects of polyphenols on the physical properties of the two films were basically the same. Significance: and novelty. The differences in physicochemical properties between gluten‐ and glutenin‐based films functionalized by polyphenols were illustrated in this study.